Penerapan Model Pembelajaran Discovery Learning dan Problematikanya pada Pembelajaran Sejarah Kebudayaan Islam di MI Tarbiyatut Tholabah - Hakim, Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
The aim of implementing the Discovery Learning learning method is an effort to create an effective learning process and improve student learning outcomes. This research uses a descriptive qualitative approach with observation, interview and documentation data collection techniques. Meanwhile, data analysis uses in-depth data analysis, namely the data reduction stage, data presentation and drawing conclusions. The aim of the research is to describe the application of the discovery learning model and its problems in learning the History of Islamic Culture at MI Tarbiyatut Tholabah Kranji. The results of the research show that the teacher applies the six steps of the discovery learning model, the results of its application are very effective, students feel happy, it trains students' critical reasoning, it doesn't seem boring. and is able to increase student learning motivation, and can improve learning outcomes. The problems that arise, the limited time, limited critical thinking of students and not all students are able to absorb the material, these findings are different from previous research which only focused on implementing learning models without any problems.